Financial strategies to promote SMEs competitiveness (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
Financial management is crucial both at an individual and business level to ensure stability and sustainable economic growth. In this context, research was conducted with the aim of designing financial strategies to enhance the competitiveness of SMEs in the commercial sector in San Martín Texmelucan, Puebla. Directors, managers, and owners of micro and small businesses were surveyed, using data from SIEM indicating the presence of 965 companies in the region, of which 65% are engaged in commerce. The results highlighted a lack of financial control in 82% of the companies, with 32% seeking external financing. 78% of SMEs expressed the need for financial analysis. In response, investment strategies were proposed to improve resource management and foster long-term competitiveness and profitability.
Keywords: finance; competitiveness; SMEs